Literatur Review: Siderophore Activity and Campability of Bacillus as Pathogen Controller of Eggplant Plant - Saputra, M. Rizki; Chatri, Moralita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Solanum melongena (eggplant) is an important cultivated vegetable crop with a very high consumer level, both in tropical and subtropical regions. Eggplant is widely favored by the public because in addition to having a good taste, it can also be made pickled and candied eggplant, and is good as a source of nutrition in supporting public health. Siderophores are metal-coating agents with low molecular mass (200-2000 Da) produced by microorganisms and plants, especially under Fe-limiting conditions. Antagonistic bacteria generally live colonizing roots an d are beneficial, because they are able to increase plant growth and induce systemic resistance. one species of the genus Bacillus spp. namely B. subtilis is able to produce amylase, protease, pullunase, chitinase, xylanase and lipase enzymes which are secondary metabolites to control pathogens and spur plant growth. This article is sourced from relevant literature studies related to the title. The purpose of writing the article is to determine the benefits of siderophores as pathogen disease control in eggplant plants. Results successfully inhibited the growth of pathogens.